PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DIMEDIASI WORK ENGAGEMENT - Nur Malinda, Selfi; Safitri, Rini (Universitas Islam Lamongan, 2023)
The purpose of this research is to determine how organizational citizenship behavior mediated by work engagement is influenced by perceptions of organizational support. This research uses quantitative methodology. The General Staff of Malang City Hall was the subject of the research. Using SmartPLS software, data was collected through questionnaires and analyzed using PLS techniques. Factors to examine include organizational citizenship, perceived organizational support, and work engagement. Based on the findings of this research, POS has no significant effect on OCB. On the other hand, POS influences work engagement, and can indirectly and significantly mediate the relationship between POS factors and OCB.